Algebra & geometry : an introduction to university mathematics - Lawson, Mark V. (Boca Raton : CRC Press, Taylor & Francis Group, 2016)
"Algebra & Geometry: An Introduction to University Mathematics provides a bridge between high school and undergraduate mathematics courses on algebra and geometry. The author shows how mathematics is more than a collection of methods by presenting important ideas and their historical origins throughout the text. He incorporates a hands-on approach to proofs and connects algebra and geometry to various applications."--
Ideas. The nature of mathematics ; Proofs ; Foundations ; Algebra redux -- Theories . Number theory ; Complex numbers ; Polynomials ; Matrices ; Vectors ; The principal axes theorem
"A Chapman & Hall book."
Includes bibliographical references (pages 347-353) and index
Keywords: Algebra; Geometry; Mathematics